Using Mosses as Bioindicators of Potentially Toxic Element Contamination in Ecologically Valuable Areas Located in the Vicinity of a Road: A Case Study - Radziemska, Maja; Mazur, Zbigniew; Bes, Agnieszka; Majewski, Grzegorz; Gusiatin, Zygmunt M; Brtnicky, Martin (International journal of environmental research and public health, 2019)
This study analyzed the impact of road transportation on the concentration of Zn, Ni, Pb, Co, and Cd in moss (Pleurozium schreberi). The study was carried out over five years near a national road running from the north to the east (Poland) in the area of Natura 2000 sites. Samples were collected at three significantly different locations: (1) near a sharp bend, (2) near a straight section of the road in a woodless area, and (3) in a slightly wooded area. At each location, moss samples were collected from sites situated 2, 4, 6, 8, 10, 12, and 14 m from the road edge. The highest Zn and Cd contents in the moss were recorded 6 m from the road edge near a sharp bend (where vehicles brake sharply and accelerate suddenly). At the same location, at a distance of 2 m, the highest Pb concentration was noted, and at a distance of 4 m from the road, the highest Ni concentration was noted. The Co concentration in the moss was the highest near the woodless straight section at a distance of 2 and 12 m from the road. The concentrations of Zn, Pb, Ni, Co (only at the woodless location), and Cd (at all locations) were significantly and negatively correlated with distance from the road.
Keywords: Bryopsida; Environmental Biomarkers; Transportation; road transportation; bioindicators; potentially toxic elements; mechy; doprava; Poland; Pleurozium schreberi; těžké kovy; Metals, Heavy; bioindikátory; Environmental Monitoring; monitorování životního prostředí; Polsko